Trânsito de saberes e campo representacional na visão dos profissionais da saúde da família e do programa de educação pelo trabalho e para a saúde - Santos, Raionara Cristina de Araujo (2010)
The Family Health Strategy (ESF) is emerging as a possible restructuring of services and new practices of intervention in health care; it requires skilled professionals to work with that framework. Within this purpose, we established the Education Programme for Work and Health (PET-Saúde), in order to integrate teaching and service activities, focusing on primary care. On this basis, the aim of this work is to apprehend the social representation of nurse, doctor and dentist (Project PET-Natal Health RN preceptors) on the ESF, while practice field of them. It is a descriptive and exploratory study, with a qualitative approach, carried out in 07 Family Health Units (USF) included in the PET-Saúde Natal (RN). The population was composed of 35 professional components of the primary care team with bachelor's degree of the USF linked to this project. The sample was composed of 05 nurses, 05 physicians and 05 dentists, for a total of 15 subjects. Data were collected through three instruments: the drawing-themed story, a semi-structured individual interviews and field diary. The data relating to the identification of the subjects were entered and tabulated by the Microsoft Excel software 2007 version. The drawing analysis and interpretation is given by the significance attributed to the resource chart from title and keywords assigned by the subjects, considering the ESF as an inductive term. The stories and interviews were transcribed and typed and then subjected to read/listen the material and a lexical analysis through Alceste. After this process, the discursive material was analyzed and discussed by theoretical and methodological feature of the Social Representations theory. The majority of health professionals were female, aged between 46 and 52 years old, married, income less than six minimum wage, time since graduation ranged from 22 to 29 years and working time in the ESF range from 02 to 11 years. From the classification system ALCESTE were selected categories identified by: Category 1 - ESF: relations and territory; Category 2 - Training and bond profile; Category 3 - Working process in the ESF; Category 4 - Articulation between teaching and service; Category 5 - Health care and disease prevention. The representational field construction, while a process, followed the logic of structural cores in existing categories. In this sense, it is clear that the ESF is an environment rich in diversity, experience and relationships with potential such as the relationship "very subject-subject" and the link established between professional-community, but also has some weaknesses such as poor working conditions, lack of popular participation and management support, thus difficulties in the achievement of teamwork. Being essential to that end, the teaching-service aimed at the formation of a new health professional able to work in the ESF. In this research, the training of the representational field encountered a diversity of structural cores, or thoughts on training, about the ESF because of the greater emphasis on the here and now of the interaction between health professionals, the ESF, the community, PET Health-UFRN and students, emphasizing that such proposals are still considered as concepts in the context of recent health and that, therefore, are not fully realized in the social imaginary